Effect of sodium carbonate and sodium phosphate on hydration of cement paste. (January 2022) - Zhang, Ting; Ma, Baoguo; Tan, Hongbo; Qi, Huahui; Shi, Tao
Abstract: Both sodium carbonate (NC) and sodium phosphate (NP) could immediately precipitate in the presence of calcium ions (Ca 2+ ), and these precipitates would deposit on the surface of cement as one layer in cement paste. However, these precipitates have different effects on the hydration of cement. In this study, effect of NC and NP on cement hydration was discussed, and the different effect between these two was investigated. Setting time, hydration heat, conductivity of cement suspension, and compressive strength of cement paste were examined, and the hydrates were analyzed with XRD and TG-DTG. The precipitates synthesized in saturated calcium hydroxide solution were characterized with XRD, TEM, and SEM. Then one model was proposed to illustrate the mechanism of the effect of NC and NP on cement hydration. The results indicated that NC accelerated cement hydration, but NP retarded it. And the results of TEM and SEM showed that calcium carbonate (the precipitate formed by NC and Ca 2+ )) could well crystalize with directional growth, there is a large amount of interspace in the calcium carbonate-based layer, which would benefit the transports of water molecules and dissolved ions. However, the calcium phosphate precipitate (the precipitate formed by NP and Ca 2+ )) seemed to have a large amount of amorphous structure with a much more compact layer structure than calcium carbonate. The difference in composition and structure of the layer was responsible for the effect of NC and NP on cement hydration. The mechanism behind accelerating effect of NC was due to the interspace in the calcium carbonate based layer which facilitated the ion dissolution of system, while that for retarding effect of NP was because the calcium phosphate-based layer formed on the surface of cement grains seemed compact enough to restrict the transports of water molecules and dissolved ions. Such consequences were expected to give deeper insight into the effect of the surficial structure of cement grains on early hydration of cement paste. Highlights: NC accelerates the early hydration of cement, but NP retard it. Both NC and NP will precipitate with calcium ions and deposit on the cement surface. The precipitate formed by NC has a large amount of interspace on the cement surface. The precipitate formed by NP forms a dense structure on the cement surface.